The Withering Away of the Physician in Medical Sociology: Medicalization, Biomedicalization, and Pharmaceuticalization - Anıl Mühürdaroğlu (İstanbul Üniversitesi Sosyoloji Dergisi)
Sociological research on medicine was initially conducted by locating physicians as the key decision-makers on health-related issues. This approach, which was furnished by the assumptions of the postwar sociology of professions, has led to a medical sociology that has rather limited space for the patient’s role in the health care process. With the emergence of a critical stance towards experts and the entire technocratic edifice of modern societies in the 1960s, medicine’s role in society became a key issue of discussion, and physicians were once again located at the forefront of the analyses on the process of medicalization, which denotes the expansion of medicine’s jurisdiction in terms of determining the “right” way of living. The medicalization process and the key role physicians play in it were questioned from the 1980s onward with new studies in medical sociology which started to pay more attention to the role of bureaucratization and commercialization of health care, patients’ influence in medicalization and the increasing influence of technoscientific advancements in shaping medical practice and our conception of health and disease in general. These new concerns have brought about new theories like biomedicalization and pharmaceuticalization, with which physicians have started to wither away in medical sociology.